Examining time use patterns in South Africa, 2000–2010. Issue 6 (2nd November 2022) - Nackerdien, Faeez; Yu, Derek
ABSTRACT: This study comprehensively examines time use patterns in South Africa by Systems of National Accounts (SNA) classification, with the aid of the 2000 and 2010 Time Use Survey (TUS) data. The empirical findings indicated that both mean SNA and non-SNA production time increased at the expense of mean non-productive time, with the former increase being attributed to work in establishments and household maintenance activities, respectively. Mean work in establishments time was particularly higher for middle-aged white male individuals who were highly educated, employed, lived in Western Cape and Gauteng, and resided in small-sized households. On the contrary, mean unpaid work time (especially household maintenance) was higher for unemployed female Africans. Furthermore, individuals in the weighted sample spent over 50% of their time on personal care whereas 20% time was spent on SNA and non-SNA production (paid and unpaid work) altogether. Lastly, all individuals spent non-zero time on personal care activities.